2018
DOI: 10.1002/adom.201800677
|View full text |Cite
|
Sign up to set email alerts
|

NiO–ZnO Nanoheterojunction Networks for Room‐Temperature Volatile Organic Compounds Sensing

Abstract: Engineering of highly performing nanomaterials, capable of rapid detection of trace concentrations of gas molecules at room temperature, is key to the development of the next generation of miniaturized chemical sensors. Here, a highly performing nanoheterojunctions layout is presented for the rapid room‐temperature chemical sensing of volatile organic compounds down to ten particles per billion concentrations. The layout consists of a 3D network of nickel oxide–zinc oxide (NiO–ZnO) p–n semiconductors with grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 43 publications
8
74
0
Order By: Relevance
“…Specifically, both samples conserve the highest sensitivity and goodness of sensor signal towards acetone molecules, rather than toluene gas. However, interestingly, the 32:1 TiO 2 /GO sample exhibits a "reversed" behavior in the case of small and polar molecules, such as acetone (Figure 5f), maybe caused by the interaction between the moisture adsorbed on the sensing material highly-hydrophilic surface [60] and the VOC molecules, and this is lost when the operating temperature is above the water condensation point, as reported by Tricoli et al [65]. Overall, the tailoring of titanium ions into tin dioxide matrix alongside with the integration of graphene oxide into the metal oxides could be exploited for the engineering of materials with higher sensing performances, especially in terms of selectivity to different VOC species.…”
Section: Vocs (Toluene and Acetone) Sensingsupporting
confidence: 58%
“…Specifically, both samples conserve the highest sensitivity and goodness of sensor signal towards acetone molecules, rather than toluene gas. However, interestingly, the 32:1 TiO 2 /GO sample exhibits a "reversed" behavior in the case of small and polar molecules, such as acetone (Figure 5f), maybe caused by the interaction between the moisture adsorbed on the sensing material highly-hydrophilic surface [60] and the VOC molecules, and this is lost when the operating temperature is above the water condensation point, as reported by Tricoli et al [65]. Overall, the tailoring of titanium ions into tin dioxide matrix alongside with the integration of graphene oxide into the metal oxides could be exploited for the engineering of materials with higher sensing performances, especially in terms of selectivity to different VOC species.…”
Section: Vocs (Toluene and Acetone) Sensingsupporting
confidence: 58%
“…Figure a–c depicts the X‐ray diffraction patterns of the ZnO thin films on glass substrates as a function of annealing temperatures. It is clear that the ZnO thin films are polycrystalline with diffraction peaks located at 31.9°, 34.5°, 36.3°, 56.7°, corresponding to the crystal planes of (100) (002) (101) (110), respectively . Obviously, the crystallinity was effectively enhanced with the increase of annealing temperature from 200 to 400 °C.…”
mentioning
confidence: 99%
“…Up to now, many working groups tried to improve the gas sensing properties of ZnO-based gas sensors by construction p - n heterojunctions. For example, Chen et al reported the fabrication of ultraporous ZnO/NiO heterojunction networks using flame synthesis and aerosol self-assemble, and studied their gas sensitivity toward volatile organic compounds (VOC) gas [ 23 ]. The reported results demonstrated that the ZnO/NiO nanoparticle networks demonstrated excellent sensitivity to acetone and ethanol gas.…”
Section: Introductionmentioning
confidence: 99%